Cliometrics in Education from a Historical and Comparative Perspective - Diebolt , Claude (Studia Oeconomica Posnaniensia, 2026)
Cliometrics in education is a young discipline. While substantial understanding has been achieved in many parts of the world, the subject has not solved its own methodological problems or made much effort to do so. Now it is back in fashion, and people are beginning to ask questions about the scope of its application, the relevance of its methods and the purposes it serves. The fact that cliometrics in education is a synthetic discipline, comprising economics (theory, history and statistics/econometrics) on the one hand and the science of education on the other, may explain some of these difficulties.